2010
DOI: 10.1038/oby.2009.487
|View full text |Cite
|
Sign up to set email alerts
|

Limited Supermarket Availability Is Not Associated With Obesity Risk Among Participants in the Kansas WIC Program

Abstract: Socioecological theory and a growing body of research suggests that geographic, racial, ethnic, and socioeconomic disparities in the prevalence of obesity are linked to disparities in the availability of food retail outlets that provide healthy food options. We examined the availability of food stores for low‐income women in Kansas and tested whether food store availability was associated with obesity using cross‐sectional, geocoded data from women participating in the Special Supplemental Nutrition Program fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 36 publications
(52 reference statements)
0
18
0
Order By: Relevance
“…27,31 Other studies of outcomes associated with food outlet availability have also produced inconsistent findings. 3242 Drewnowski et al found that obesity risk was not associated with proximity of supermarkets that retail healthy food, but rather the type of supermarket and the prices of the food items offered. 33 Zenk et al observed that presence of certain neighborhood food environment indicators influenced fruit and vegetable intake, while Aggarwal et al and Boon-Heinonen et al found that fruit and vegetable consumption was not associated with market availability.…”
Section: Discussionmentioning
confidence: 99%
“…27,31 Other studies of outcomes associated with food outlet availability have also produced inconsistent findings. 3242 Drewnowski et al found that obesity risk was not associated with proximity of supermarkets that retail healthy food, but rather the type of supermarket and the prices of the food items offered. 33 Zenk et al observed that presence of certain neighborhood food environment indicators influenced fruit and vegetable intake, while Aggarwal et al and Boon-Heinonen et al found that fruit and vegetable consumption was not associated with market availability.…”
Section: Discussionmentioning
confidence: 99%
“…Low-income and minority populations in the USA are more likely to have limited supermarket access combined with saturation of fast-food establishments and convenience stores (7,8) , a pattern that has not consistently been observed in other wealthy countries (9) . Although evidence is mixed (10)(11)(12)(13)(14) , poor food access conditions have been linked to lower fruit and vegetable intakes (15)(16)(17) and higher risk of obesity in adults and adolescents (7,(18)(19)(20)(21) . Even when physical access to healthy foods is available, higher prices and poor quality may be meaningful barriers to improving nutrition and health in vulnerable populations in many countries (22)(23)(24)(25)(26)(27)(28) .…”
mentioning
confidence: 99%
“…Ahern and colleagues observed that availability of grocery stores was associated with increased adult obesity prevalence in non-metro counties [49]. Ford and colleagues reported that presence of a supermarket within 1 mi of a participant’s residence was associated with increased risk of obesity among women living in areas with a moderate population density [55]. However, slightly more evidence exists supporting the latter.…”
Section: Food Retail Environment and Obesity Riskmentioning
confidence: 99%
“…Additionally, Morland and colleagues reported that the presence of convenience stores was associated with higher obesity prevalence [62]. Despite the studies yielding statistically significant results in the desired direction [51, 54, 56, 62, 6568], a fair percentage of studies observed null findings [52, 55, 57, 58, 6971]. Contrary to most findings, studies reporting unexpected or negative results also exist in the literature [49, 50, 55, 57].…”
Section: Food Retail Environment and Obesity Riskmentioning
confidence: 99%